The Importance of Parental Influence in the Formation of Children’s Character - Inggis, Maria Praviyanti; Dhiu, Margaretha (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The development of children’s character is a fundamental process shaped primarily by the family environment, with parents serving as the main source of values, norms, and behavioral models. However, modern social dynamics such as increased digital distractions and declining emotional connectedness between parents and children pose new challenges to the optimal formation of character. This study employs a qualitative method using a literature review approach to examine existing empirical and theoretical findings on parental influence in shaping children’s character. Data were gathered from indexed journals, academic books, research reports, and policy documents and analyzed through thematic identification, conceptual categorization, and integrative synthesis.The purpose of this study is to explain the mechanisms through which parents shape children’s character, particularly through parenting practices, family communication, moral modeling, and the internalization of cultural values. The findings indicate that consistent and responsive parental involvement significantly contributes to the development of children’s moral reasoning, discipline, empathy, and social–emotional competencies. These results underscore the central role of the family as the foundation of character education and highlight the need to strengthen parenting quality, promote school–family collaboration, and provide policy support that enhances parental literacy in navigating contemporary parenting challenges.